Awareness and attitudes of juvenile delinquents toward drug-related problems and extrajudicial killings in the Philippines. - Panaligan, Just Lynn D.
The study sought to identify and describe the socio-demographic profile, awareness, and attitudes of juvenile delinquents or children in conflict with the law (CICL). Forty-five (45) respondents aged 15-23 years old were purposively selected from the Regional Rehabilitation Center for the Youth (RRCY); an exclusive for boys rehabilitation center. There were six (6) instruments administered to study the variables under investigation and one-on-one interviews were conducted to further understand the answers of the respondents. Results revealed that majority of the juvenile delinquents were Roman Catholics, were mostly firstborns with a number of 4 to 6 siblings and have committed offenses at age 16. Furthermore, most of their crimes were either drug-related or murder. The pre-dominant reason for quitting school is because of peer influence and financial problems, while the salient reasons for why the offenses were committed were either because of conflict that was also caused by peer influence, and intoxication. On the other hand, the respondents possess high awareness toward the drug-related problems and the alleged extrajudicial killings. They have also expressed a negative attitude toward both issues.